Computer art: software art design - Suzete Venturelli (ANIAV, 2021)
The article presents artistic works developed at the Computational Art Research Laboratory Media Lab / UnB, carried out as a team, under my coordination. The artistic and theoretical production sought to defend the idea that computational art is a new form of appreciated art, based on the assumption that it contains many of the components of a complete philosophy of an art form, which can be summarized in four basic references: one definition, an ontology, aesthetic characteristics, and the recognition of its status as art. What is currently called computational art is based on the observation that experiments in this domain involve more general common issues, in statu nascendi, to the artistic and technoscientific domains, which provide the structuring modes, the methodology and the programming techniques, introduced in the process. Computational art does not always use the computer, sometimes it is based on logical-mathematical operations only. However, computers had a profound impact on the arts, and in order to carry out a partial synthesis, based on a global theory of aesthetics today, a set of artistic works was selected that encompass the following subjects: the computer as an amplifier complexity (computational methods of creation); computational language; the developer artist; computational art as art of the crowd and not of the individual; laboratory work; software art (presentation and analysis of historical algorithms such as permutation, random, etc.); the appreciation of the human-computer interface (highlighting the importance of the game), which enabled greater public interactivity with the artistic work; the appropriation of the media for artistic purposes; the artistic engagement with social and ecological issues originated by technoscientific advances and the society's computerization policy and propositions related to the future, formulated philosophically in the post-biological era. We sought to develop poetics that resulted from the collaboration between living beings and machines.